Contract protection against encroachment of other parties: A search for theoretical grounds - V.G. Golubtsov (Ученые записки Казанского университета: Серия Гуманитарные науки)
Analysis of problems related to the invasion of third parties into other people’s contractual relations has rapidly acquired relevance in both theoretical and practical terms. The main issues related to them have already come into the research focus, but some of the important aspects remain understudied. The article supports the prevailing view that Russian legislators should pay more attention to the above-stated problems. The known theoretical approaches to understanding and solving them are analyzed. Interventional behavior is considered from the perspective of national tort law. The following theoretical conclusions are drawn: the traditional understanding of civil liability adopted in the Russian doctrine, as well as the existing systematics and technical and legal techniques of the Russian tort law, serve as an obstacle for introduction of such type of tort as causing harm to the parties of contractual relations by third parties into this institution. These conclusions are confirmed by the results of a comparison of the Russian tort law system with the English one, which is among the three (along with those in Germany and France) most developed systems in the world and employs such methods of responding to the invasion of third parties in contractual relations that are most widely discussed in the modern national discourses.